Advances in the genetics of myasthenia gravis: insights from cutting-edge neuroscience research - Yixian, Zheng; Hai, Wang; Xiuying, Liu; Jichun, Yan (Frontiers in Medicine, 2025)
Myasthenia gravis (MG) is an autoimmune disorder involving complex interactions between genetic and environmental factors. Genome-wide association studies (GWAS), transcriptome-wide association studies (TWAS), and other methods have identified multiple novel susceptibility loci and genes, providing crucial insights into the genetic etiology of MG. Moreover, the pivotal roles of epigenetic mechanisms, such as DNA methylation, histone modifications, and non-coding RNAs, in the pathogenesis of MG are gradually being unveiled. This review comprehensively summarizes the latest advances in MG genetic research, focusing on the discovery and validation of susceptibility genes, genetic heterogeneity and subtype-specific genetic factors, gene–environment interactions, epigenetic mechanisms, and progress in genetics-based diagnostic and prognostic biomarkers.